PARENTS' PERCEPTION OF THE USE OF YOUTUBE CONTENT IN SUPPORTING EARLY CHILDHOOD COGNITIVE STIMULATION - Sheila Citra Suci; Dedi Kuswandi; Yudhitia Dian Putra (Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta, 2026)
This study aims to analyze parents' perceptions of the use of YouTube content to support cognitive stimulation in early childhood. The study used a qualitative approach with a descriptive design. The study subjects consisted of 15 parents of children aged 2–6 years who use YouTube as a learning medium. Data were collected through interviews, participant observation, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that parents view YouTube as a medium that has the potential to support children's cognitive development, particularly in color recognition, numbers, and early language skills, if the content used is age-appropriate, educational, and interactive. However, the effectiveness of YouTube use is greatly influenced by the level of parental involvement in selecting, supervising, and accompanying children during media use. Parents who actively provide support tend to have children with more optimal cognitive development compared to those who are less involved. This study confirms that parental perceptions and practices are key factors in maximizing the benefits of digital media for early childhood.